Menolak Wabah dalam Serat Ronggo Sutrasno Karya Sunan Kalijaga - Muhammad Abdullah (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
One of the Javanese texts with esoteric value is the Ronggasutrasna Kidungan Fiber which is kept by the Surakarta Sastra Lestari Foundation. Serat Kidungan Ronggasutasna is a Javanese script in which there is a text in the form of fibers written by Sunan Kalijaga written together with Ronggasutrasna and then published by Tan Gun Swi. This manuscript is a compilation of a number of songs including Rumeksa Ing Wengi (KRIW), Padanghyangan Kidungan (and those of the dhedhemit ratuning), and other hymns. However, the KRIW text is not an original manuscript written by Sunan Kalijaga. This is evidenced by the existence of other KRIW texts in PNRI presented in handwriting. Serat Kidung Ranggasutrasna is the song of the 'kid' of old fibers which is a representation of esoteric values and Islamic symbolism of the spiritual messages of Kanjeng Sunan Kalijaga. After the authors examined the contents of the text, the authors concluded that most of the Ranggasutrasna's fiber of the Kidungan text contains the magic power plan in the form of spells of rebel, repellent witchcraft, sorcery, babysitting, escaping from the bondage of debt, self defense, war ethos, worship ethos, and treatment system in Javanese culture. Fiber Kidung Ranggasutrasna belongs to the piwulang script which is presented in the form of Javanese song.Keywords: Song of Ranggasutasna; esoteric; magical power; local wisdom. Intisari Salah satu naskah Jawa yang bernilai esoteris adalah Serat Kidungan Ronggasutrasna yang disimpan oleh Yayasan Sastra Lestari Surakarta. Serat Kidungan Ronggasutasna adalah sebuah naskah Jawa yang di dalamnya terdapat sebuah teks berbentuk serat hasil tulisan Sunan Kalijaga yang disusun bersama Ronggasutrasna dan kemudian diterbitkan oleh Tan Gun Swi. Naskah ini merupakan kompilasi dari beberapa kidungan yang di antaranya Kidungan Rumeksa Ing Wengi (KRIW), Kidungan Padanghyangan (danyanghyangan para ratuning dhedhemit), dan kidung-kidung lainnya. Namun teks KRIW bukan merupakan naskah asli tulisan Sunan Kalijaga. Hal ini dibuktikan dengan adanya teks KRIW lain dalam PNRI yang disajikan dalam tulisan tangan. Serat Kidung Ranggasutrasna merupakan nyanyian 'kidungan' serat kuna yang merupakan representasi nilai-nilai esoteris dan simbolisme Islam dari pesan-pesan spiritual Kanjeng Sunan Kalijaga. Setelah penulis meneliti isi teks, penulis menyimpulkan bahwa sebagian besar teks Serat Kidungan Ranggasutrasna berisi tentang piwulang kekuatan gaib yang berupa mantra-mantra tolak balak, penolak santet, tenung, penjaga bayi, kluar dari belenggu hutang, bela diri, etos perang, etos ibadah, dan sistem pengobatan dalam budaya Jawa. Serat Kidung Ranggasutrasna tergolong ke dalam naskah piwulang yang disajikan dalam bentuk tembang Jawa.Kata kunci:  Kidung Ranggasutasna; esoteris; kekuatan gaib; kearifan lokal.